The prevalence and impact of violence and sexual harassment of registered nurses in the workplace. - Williams M (Chart)
A study to determine the prevalence and impact of violence and sexual harassment experienced by registered nurses (RNs) in their workplaces was conducted in Illinois. A random sample of 1130 RNs were selected to participate in the mail survey. The instrument used was the Nurse Assault Survey originally developed by the Nurse Assault Project Team in Ontario, Canada, and modified by this researcher. Three hundred forty-five subjects completed the survey for a response rate of 30%. The sampling error was +/- 5%. Nearly 70% (68.9%) of the respondents were between 30 and 49 years old. Seventy-five percent had more than ten years experience. Sixty percent had been in their present position for five years or less, and most (80%) had a nursing baccalaureate or associate degree or less as their highest educational level. Sixty-four percent (63.6%) of those responding reported personal experience with sexual harassment. Perpetrators of the harassment were most often patients/clients (72.8%) followed by physicians (57.9%). Seventy percent (70.9%) of those that had been harassed reported 1-12 experiences within the previous year. Nurses who worked in community home health (64.7%) and occupational health (60.7%) were most often harassed. In hospital settings, harassment was most frequently reported in the operating room, medical-surgical area, and the emergency room. About one-third of those that had been sexually harassed had also been physically assaulted. Less than 40% (38.5%) of the survey respondents knew their employers had a policy on sexual harassment. Almost half (47.6%) were unsure. A quarter (25.2%) of the respondents had actually experienced physical assault, while an additional 3.8% had been sexually assaulted. Forty-two percent (42%) had been subjected to threats of physical harm. Patients were almost always (93.4%) the perpetrators of physical assault, with nearly a third (30.8%) being female. Physicians, however, were the most frequent perpetrators of sexual assault. Results of this survey demonstrate that registered nurses need to take an active role in fostering a work environment free from violence and sexual harassment. They need to be knowledgeable about institutional policies, and where none exist, they should work with administrators to develop them. Educational programs to help nurses (and other employees) deal with sexual harassment need to be developed. Aggression management techniques must be learned, environmental precautions must be taken and procedures and protocols for handling violence in health care settings must be implemented. Curricula in nursing education programs should address issues of workplace violence and sexual harassment. Research efforts must focus on differences in patterns of violence and sexual harassment in various work settings. About the author Margie Williams is a member of the INA District 9 and is Director of the Nursing Program at Sangamon State University in Springfield.